Pengaruh Budgetary Slack, Transparansi, Sistem Akuntansi Manajemen, Asimetri Informasi, dan Job Relevant Information (JRI) terhadap Kinerja Manajerial pada CV. Anugerah Darma Mandiri Jember - Nikita Amirah Aulia; Nurshadrina Kartika Sari; Ratih Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
This study aims to analyze the effect of budgetary slack, transparency, management accounting system, information asymmetry and job relevant information (JRI) on managerial performance at CV. Anugerah Darma Mandiri Jember. The population in this study are all employees and managers at CV. Anugerah Darma Mandiri Jember. The sampling technique in this study is the saturated sample technique. The data used in this study is primary data, namely data obtained from respondents directly through questionnaires. The data analysis method used is Multiple Linear Regression analysis with the help of SPSS processing. The result showed that budgetary slack had no partial effect on managerial performance at CV. Anugerah Darma Mandiri Jember. Meanwhile, transparency, management accounting system, information asymmetry and job relevant information (JRI) partially affect managerial performance in CV. Anugerah Darma Mandiri Jember. Simultaneously, budgetary slack, transparency, management accounting system, information asymmetry and job relevant information (JRI) affect managerial performance in CV. Anugerah Darma Mandiri Jember.